Chemical and mineralogical characterization of late chalcolithic pottery (ca. 3700–3300 BCE) from southwest Anatolia (Türkiye) - TUNCALI YAMAN, TUTKU (My University, 2023)
This paper presents the results of chemical and petrographic investigations on the late chalcolithic (ca. 3700–3300 BCE) pottery from the Burdur Lake region in southwest Anatolia (Türkiye). Twenty-one ceramic sherds and a clay lump from four different levels of the late chalcolithic site of Kuruçay Höyük (Burdur) were examined with thin section petrography, XRF, and XRD to illuminate the element and mineral compositions of the ceramics. The chemical compositions and their statistical evaluation demonstrate the continuous use of at least two local clay sources within each different phase of the late chalcolithic. While sources stay the same, petrographic thin section analysis implies a change in the clay preparation techniques. This is visible via the homogeneity of the clay matrix and the existence of shell and lithic inclusions in the paste. About the end of the late chalcolithic period, clay preparation appears to be enhanced conceivably with the changing technological setting of the period toward the early bronze age.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Southwest Anatolia; Late chalcolithic; Pottery production; Petrographic thin section; XRF; XRD